Pengaruh Promosi Digital dan Citra Sekolah Terhadap Minat Pendaftaran Siswa Baru MTs Hudatul Falah Ciseeng - Sofyan, Ahmad; Igo, Arif (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The development of digital technology has transformed marketing strategies in education, including efforts to increase student enrollment interest through digital promotion and the establishment of a positive school image, this study aims to analyze the influence of digital promotion and school image on student enrollment interest at MTs Hudatul Falah Ciseeng, the research method used is a quantitative approach with a survey technique involving 150 respondents, data were collected through questionnaires that had been tested for validity and reliability, data analysis was conducted using descriptive statistics, normality tests, and multiple linear regression, the results show that digital promotion and school image have a positive and significant effect both partially and simultaneously on student enrollment interest, with a coefficient of determination of 50% indicating the contribution of both variables in explaining variations in enrollment interest, the discussion indicates that digital promotion increases visibility and access to information while school image builds trust and positive perceptions among the community, the conclusion emphasizes the importance of integrating digital promotion strategies with strengthening school image to enhance student enrollment interest, therefore schools need to develop adaptive and technology-based marketing strategies to remain competitive.